Adsorption and Thermodynamics Studies of Corrosion Inhibition on Carbon Steel using Pumpkin Pod Extract (Telfairia occidentalis) - Okewale, A. O.; Adebayo, A. T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
In this study, the inhibition effect of ethanolic extract of pumpkin pod (Telfairia occidentalis) on the corrosion of carbon steel in acidic medium was investigated using weight loss method at 308K - 348K. The energy of activation, adsorption and thermodynamics parameters such as enthalpy, entropy, and Gibb’s free energy were evaluated from the results of temperature studies. The activation enthalpy of corrosion process increases from 28.782kJ/mol to 62.678kJ/mol. As the temperature increased, the inhibition efficiency decreased. The adsorption of pumpkin pod extract on carbon steel was found to best fit Langmuir, and Freundlich adsorption isotherms. The activation energy of adsorption and Gibb’s free energy values indicated an endothermic and strong spontaneous adsorption of the pumpkin pod extract on the surface of carbon steel respectively. Scan Electron Microscope (SEM) analyses showed that Pumpkin pods (Telfairia occidentalis) extract protected the surface of the metal from corrosion by forming a protective layer on the metal surface.